Effects of Preanhepatic Glucose-Insulin Infusion on Metabolic and Hemodynamic Outcomes in Liver Transplantation: A Randomized Clinical Trial - Moshari , Mohammadreza; Gharehbeglou, Mohammad; Dabir , Shideh; Vosoughian, Maryam; Dahi, Mastaneh; Dabbagh , Ali; Tabashi, Soudeh; Ariannik , Mohsen; Firoozeh Madadi; Ordoni Avval, Jamshid (Galen Medical Journal, 2025)
Background: Liver transplantation is a complex procedure requiring meticulous perioperative management to optimize outcomes. The administration of glucose-insulin solutions during the preanhepatic phase may influence hemodynamic and metabolic stability. This study aimed to evaluate the effects of dextrose-insulin infusion on hemodynamic, metabolic, and clinical outcomes in liver transplant recipients. Materials and Methods: A randomized, double-blinded clinical trial was conducted on 88 patients (1:1 allocation) undergoing liver transplantation at Taleghani Hospital, Iran. The intervention group received dextrose 50% (1g/kg) and insulin (1u/kg), while the control group received normal saline. Hemodynamic parameters (cardiac output, vascular resistance), metabolic markers (glucose, potassium, lactate), and clinical outcomes (hospital stay, complications) were assessed across preanhepatic, anhepatic, and reperfusion phases. Statistical analysis was performed using SPSS v27.0. Results: The intervention group demonstrated significantly higher cardiac output (6.95±1.66 vs. 5.56±2.02 L/min, P<0.001) and lower inotropic requirements (65.9% vs. 88.6%, P=0.018) during the anhepatic phase. Postoperatively, the intervention group had reduced ALT (P=0.038), AST (P=0.019), bilirubin (P=0.021), BNP (P=0.002), and lactate (P<0.001). No differences were observed in hospital stay, ICU duration, or complication rates. Conclusion: Dextrose-insulin administration during liver transplantation improves intraoperative hemodynamics and reduces postoperative metabolic stress without increasing adverse events.